Improved efficiency of reversed‐phase carbon/nanodiamond/polymer core–shell particles for HPLC using carbonized poly(divinylbenzene) microspheres as the core materials. Issue 24 (December 2013) - Hung, Chuan‐Hsi; Wiest, Landon A.; Singh, Bhupinder; Diwan, Anubhav; Valentim, Michael J. C.; Christensen, James M.; Davis, Robert C.; Miles, Andrew J.; Jensen, David S.; Vail, Michael A.; Dadson, Andrew E.; Linford, Matthew R.
<x xml:space="preserve">Abstract</x> Here, we report efficiencies up to 112 000 plates per meter (a reduced plate height, h, of 2.22) for RP, carbon/nanodiamond/aminopolymer particles using conventional injection conditions in HPLC. This efficiency greatly exceeds our best previously reported value of 71 000 N/m (h = 3.52). The carbon cores used in this study were derived from carbonized poly(divinylbenzene) spheres that were either made in‐house by a two‐step polymerization procedure or obtained commercially. The resulting particles showed good uniformity and were oxidized in nitric acid to increase their dispersability. X‐ray photoelectron spectroscopy confirms particle oxidation and subsequent aminopolymer deposition. Layer‐by‐layer (LbL) growth of poly(allyamine) and nanodiamond was demonstrated to produce core–shell particles. After LbL growth, the particles were functionalized, sieved, and packed into columns. The column functionalization and packing were reproducible. Van Deemter curves indicated that the commercially obtained poly(divinylbenzene) spheres outperformed those synthesized in our laboratory. The columns appear to be stable at 120°C in a pH 11.3 mobile phase. Longer columns (2.1 × 50 mm) than previously reported were packed. Four essential oils were separated by gradient elution.